A comparative study of the subject in Jacques Lacan and Zhuangzi. Issue 3 (3rd July 2017) - Wang, Quan
ABSTRACT: Jacques Lacan has creatively grafted Zhuangzi's concept of the subject on the Western tradition of Logo-centrism. Lacan rewrites the triangle positions of the subject as the Real, the Imaginary, the Symbolic, expresses them in the vocabulary of detective stories, and achieves his scholarly reputation. The insufficiency of his theory could be redressed by Zhuangzi's idea of 'the poetics of oneness.' For Zhuangzi, a man can forget his 'Social I' and 'Corporeal I, ' arrive at the phase of 'the equality of things' in his symbiotic fusion with the surrounding things. These two thinkers complement each other and enrich our understanding of the subject.